2014
DOI: 10.3174/ajnr.a4187
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility-Weighted Imaging in Pediatric Arterial Ischemic Stroke: A Valuable Alternative for the Noninvasive Evaluation of Altered Cerebral Hemodynamics

Abstract: BACKGROUND AND PURPOSE: SWI provides information about blood oxygenation levels in intracranial vessels. Prior reports have shown that SWI focusing on venous drainage can provide noninvasive information about the degree of brain perfusion in pediatric arterial ischemic stroke. We aimed to evaluate the influence of the SWI venous signal pattern in predicting stroke evolution and the development of malignant edema in a large cohort of children with arterial ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
6
19
0
Order By: Relevance
“…S-D mismatch, as another imaging characteristic of PHVS, was considered the penumbra in the reperfusion window period and could be salvageable through the reperfusion therapy or due to the evolution of infarct [12, 23]. The S-D mismatch was also presented beyond the reperfusion window and might predict the stroke progression in pediatric patients [24]. Another study found that S-D mismatch was correlated with good prognosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…S-D mismatch, as another imaging characteristic of PHVS, was considered the penumbra in the reperfusion window period and could be salvageable through the reperfusion therapy or due to the evolution of infarct [12, 23]. The S-D mismatch was also presented beyond the reperfusion window and might predict the stroke progression in pediatric patients [24]. Another study found that S-D mismatch was correlated with good prognosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…[42, 46] These results suggest that SWI-DWI mismatch may be useful in patients who cannot receive contrast for PWI.…”
Section: Clinical Applicationsmentioning
confidence: 97%
“…[41] SWI also allows early detection of hemorrhagic transformation of stroke. [4244] The presence of intra-arterial thrombus can present on GRE/SWI as intra-arterial low signal and vessel diameter enlargement relative to the contralateral vessel, also termed as “the susceptibility sign”. [41, 43] Infarct/peri-infarct tissue can also demonstrate differences in perfusion parameters secondary to steno-occlusive disease using DSC perfusion.…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Thus, noncontrast MR perfusion methods such as arterial spin labelled (ASL) are used more frequently in the pediatric population 48. Susceptibility weighted imaging (SWI) is also a promising tool in childhood AIS, with mismatch of diffusion and hypointense venous SWI signal predicting stroke progression 49. SWI reflects blood oxygenation levels, and SWI values in the veins can provide an alternative assessment of degree of brain perfusion and the perfusion-diffusion mismatch.…”
mentioning
confidence: 99%